Etika Kristen tentang Perceraian: Analisis Teologi dan Implikasinya bagi Pelayanan Keluarga di Konteks Ketapang, Kalimantan Barat - Mispan Mispan; Hapyvania Tenda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
Divorce has become an increasingly common reality in Christian family life and poses serious challenges for the church in carrying out pastoral family ministry. Theologically, divorce stands in tension with Christian ethics, which views marriage as a sacred and covenantal institution established by God. This article aims to analyze Christian ethics regarding divorce from a biblical theological perspective and to examine its implications for family ministry within the context of Ketapang, West Kalimantan. This study employs a qualitative research method with a theological-normative and contextual approach through a literature review of biblical texts, theological books, and scholarly journals. The findings indicate that Scripture affirms marriage as God’s ideal will, while divorce is understood as a consequence of human sinfulness and relational brokenness. In the context of Ketapang, social, economic, and cultural factors contribute significantly to the vulnerability of families to divorce. Therefore, the church is called to develop a contextual family ministry that not only upholds Christian ethical norms but also embodies love, justice, forgiveness, and restoration for broken families. This article emphasizes that Christian ethics concerning divorce must be practiced pastorally and transformatively within the life of the local church.